Mosquito CYP4C21 knockout reduces dengue virus and Zika virus replication in Aedes aegypti cells - Xiaoxue Xie; Di Wang; Bo Li; Manjin Li; Dan Xing; Teng Zhao; Xinyu Zhou; Chunxiao Li (Elsevier, 2023)
Aedes aegypti (Ae. aegypti) is a major vector of dengue virus (DENV) and Zika virus (ZIKV). Understanding the complex interaction mechanisms between mosquito vectors and arboviruses is essential to interrupt virus transmission. This study constructed CYP4C21 knockout (KO) Aag2 cells (Ae. aegypti cells) and confirmed that CYP4C21 KO reduced DENV2 and ZIKV copies in Aag2 cells, which suggests that CYP4C21 may play an important role in mosquito infection with arboviruses. Furthermore, it is the first report of the CYP4 family related to viral infection, which lays the foundation for exploring the role of the CYP4C21 in the interaction of Ae. aegypti and arbovirus and provides novel insights into the function of cytochrome family proteins.